Pacifists, Peace Democrats, and the Politics of Perfection in the Civil War Era - Curran, Thomas F. (A journal of church and state, 1996)
Thomas F. Curran; Pacifists, Peace Democrats, and the Politics of Perfection in the Civil War Era, Journal of Church and State, Volume 38, Issue 3, 1 July 1996,